Novel loss of function mutation in TUBA1A gene compromises tubulin stability and proteostasis causing spastic paraplegia and ataxia - Riccardo Zocchi; Emanuele Bellacchio; Michela Piccione; Raffaella Scardigli; Raffaella Scardigli; Valentina D’Oria; Stefania Petrini; Kristin Baranano; Enrico Bertini; Antonella Sferra (Frontiers in Cellular Neuroscience, 2023)
Microtubules are dynamic cytoskeletal structures involved in several cellular functions, such as intracellular trafficking, cell division and motility. More than other cell types, neurons rely on the proper functioning of microtubules to conduct their activities and achieve complex morphologies. Pathogenic variants in genes encoding for α and β-tubulins, the structural subunits of microtubules, give rise to a wide class of neurological disorders collectively known as “tubulinopathies” and mainly involving a wide and overlapping range of brain malformations resulting from defective neuronal proliferation, migration, differentiation and axon guidance. Although tubulin mutations have been classically linked to neurodevelopmental defects, growing evidence demonstrates that perturbations of tubulin functions and activities may also drive neurodegeneration. In this study, we causally link the previously unreported missense mutation p.I384N in TUBA1A, one of the neuron-specific α-tubulin isotype I, to a neurodegenerative disorder characterized by progressive spastic paraplegia and ataxia. We demonstrate that, in contrast to the p.R402H substitution, which is one of the most recurrent TUBA1A pathogenic variants associated to lissencephaly, the present mutation impairs TUBA1A stability, reducing the abundance of TUBA1A available in the cell and preventing its incorporation into microtubules. We also show that the isoleucine at position 384 is an amino acid residue, which is critical for α-tubulin stability, since the introduction of the p.I384N substitution in three different tubulin paralogs reduces their protein level and assembly into microtubules, increasing their propensity to aggregation. Moreover, we demonstrate that the inhibition of the proteasome degradative systems increases the protein levels of TUBA1A mutant, promoting the formation of tubulin aggregates that, as their size increases, coalesce into inclusions that precipitate within the insoluble cellular fraction. Overall, our data describe a novel pathogenic effect of p.I384N mutation that differs from the previously described substitutions in TUBA1A, and expand both phenotypic and mutational spectrum related to this gene.